Pathways to language : from fetus to adolescent - Karmiloff, Kyra (Developing child., 2002)
Our journey to language begins before birth, as babies in the womb hear clearly enough to distinguish their mother's voice. Canvassing a broad span of experimental and theoretical approaches, this book introduces new ways of looking at language development. A remarkable mother-daughter collaboration, Pathways to Language balances the respected views of a well-known scholar with the fresh perspective of a younger colleague prepared to challenge current popular positions in these debates. The result is an unusually subtle, even-handed, and comprehensive overview of the theory and practice of language acquisition, from fetal speech processing to the development of child grammar to the sophisticated linguistic accomplishments of adolescence, such as engaging in conversation and telling a story. With examples from the real world as well as from the psychology laboratory, Kyra Karmiloff and Annette Karmiloff-Smith look in detail at the way language users appropriate words and grammar. They present in-depth evaluations of different theories of language acquisition. They show how adolescent usage has changed the meaning of certain phrases, and how modern living has led to alterations in the lexicon. They also consider the phenomenon of atypical language development, as well as theoretical issues of nativism and empiricism and the specificity of human language. Their nuanced and open-minded approach allows readers to survey the complexity and breadth of the fascinating pathways to language acquisition.